Knowledge of modifiable risk factors for cardiovascular diseases among university undergraduates in Ibadan, Nigeria - Oyewole, Oyediran Emmanuel; Solabi, Ayodele (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Undergraduates in many institutions live a lifestyle that could predispose them to non-communicable diseases (NCDs) including cardiovascular-related. Previous studies on modifiable risk factors (MRFs) against NCDs had focused mainly on adults, whereas young people should be prime targets for prevention programmes. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. This study was aimed at investigating knowledge of MRFs against cardiovascular diseases (CVDs) among university undergraduates in Ibadan, Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A descriptive cross-sectional design was adopted, where 500 undergraduates participated. Data were collected using Focus Group Discussion (FGD) guide and validated questionnaire. Data analyses were conducted using thematic approach and bivariate methods at 5% levels of significance, respectively. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Mean age was 22.8±3.0 years and 51.4% were females. The majority reported that their fathers (82.8%) and mothers (83.0%) had no hypertension history. The FGD revealed that students were knowledgeable of MRFs and preventive behaviours but still engaged in unhealthy lifestyle practices. The MRFs identified included excessive alcohol consumption (85.4%), unhealthy diet (77.6%), physical inactivity (75.2%) and smoking (70.2%). Respondents (56.4%) had good knowledge of MRFs against CVDs; 57.0% had fair lifestyle practices and 54.8% had good knowledge of preventive behaviour against CVDs. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Gender was significantly associated with knowledge of CVDs preventive behaviours. Institutional-based lifestyle modification programmes, using peer group education is suggested.